Introduction to Experimental Particle Physics - Fernow, Richard Clinton (Cambridge University Press, 1986)
This book brings together the most important topics in experimental particle physics in the late twentieth century to give a brief but balanced overview of the subject. The author begins by reviewing particle physics and discussing electromagnetic and nuclear interactions. He then goes on to discuss three nearly universal aspects of particle physics experiments: beams, targets, and fast electronics. The second part of the book treats in detail the properties of various types of particle detector, such as scintillation counters, Cerenkov counters, proportional chambers, drift chambers, sampling calorimeters, and specialized detectors. Wherever possible the author attempts to enumerate the advantages and disadvantages of performance. Finally, he discusses aspects of specific experiments, such as properties of triggers, types of measurement, spectrometers, and the integration of detectors into coherent systems. First published in 1986, this title has been reissued as an Open Access publication.